Elucidating the Dual Mode of Action of Dipeptidyl Enoates in the Inhibition of Rhodesain Cysteine Proteases. Issue 39 (27th May 2021) - Arafet, Kemel; González, Florenci V.; Moliner, Vicent
Abstract: A computational study of the two possible inhibition mechanisms of rhodesain cysteine protease by the dipeptidyl enoate Cbz‐Phe‐Leu‐CH=CH−CO2 C2 H5 has been carried out by means of molecular dynamics simulations with hybrid QM/MM potentials. The low free energy barriers confirm that the Cys25 residue can attack both Cβ and C1 atoms of the inhibitor, confirming a dual mode of action in the inhibition of the rhodesain by enoates. According to the results, the inhibition process through the Cys25 attack on the Cβ atom of the inhibitor is an exergonic and irreversible process, while the inhibition process when Cys25 attacks on the C1 atom of the inhibitor is and exergonic but reversible process. The interactions between the inhibitor and rhodesain suggest that P2 is the most important fragment to consider in the design of new efficient inhibitors of rhodesain. These results may be useful for the design of new inhibitors of rhodesain and other related cysteine proteases based on dipeptidyl enoates scaffolds. Abstract : A QM/MM computational study of two possible inhibition mechanisms of rhodesain cysteine protease by the dipeptidyl enoate Cbz‐Phe‐Leu‐CH=CH−CO2 C2 H5 confirms the dual mode of action of this family of inhibitors. Efforts focused on increasing the interaction with the residues of the S2 pocket of rhodesain could be used as a guide to design new dual inhibitors with greater selectivity and affinity.